To Madagascar and back: long‐distance, return migration across open ocean by a pregnant female bull shark Carcharhinus leucas. Issue 6 (29th October 2015) - Lea, J. S. E.; Humphries, N. E.; Clarke, C. R.; Sims, D. W.
Abstract : A large, pregnant, female bull shark Carcharhinus leucas was tracked migrating from Seychelles across open ocean to south‐east Madagascar, c. 2000 km away, and back again. In Madagascar, the shark spent a prolonged period shallower than 5 m, consistent with entering estuarine habitat to pup, and upon return to Seychelles the shark was slender and no longer gravid. This represents an unprecedented return migration across the open ocean for a C. leucas and highlights the need for international collaboration to manage the regional C. leucas population sustainably.